Digital revolution in Arabic Language teaching and learning - Nik Mat, Nik Mahfuzah; Amzah, Rodhiah; Halim, Nurul Syafawani; Mohd Salim, Mohd Nur Fitri; Wan Ismai, Wan Nurul Fatihah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Digital technology has transformed the education landscape, including Arabic Language teaching, which used to rely on conventional methods such as rote memorisation, writing exercises, and drilling. Moreover, digital approaches enhance the learning experience through the use of multimedia, gamification, and online self-learning methods. The digital learning approach in teaching the Arabic language offers various benefits. According to Badarudin et al. (2023), the use of digital storytelling and role-plays significantly aids Arabic vocabulary acquisition among students.